Online Student Mentoring System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mentoring means sharing knowledge with people around us, it is a professional way ofexpressing our skills and letting others and ourselves. Educating others with the knowledgewe have and that to done in a virtual platform is one of the main reasons of the onlinementoring system. These are basically for students nowadays who are into an online platformand looking after the performance has become much more difficult than usual, in this casethis system comes handy. This promotes active engagement of students in both academic andtheir non-academic activities. This Application replaces the conventional and inconvenientmethod of clearing doubts in classes which involves the mentor and student to be physicallypresent at the same time. In this context arises the importance of our application. Thisapplication bridges the existing gap between mentor and students due to the time constraints.